Compare the Effect of Inhaled Corticosteroids and Systemic Corticosteroids on Sputum Microbiome of AECOPD - Ma, Nan; Qi, Yujing; Liang, Xiaona; Bai, Jing; Deng, Jingmin; Li, Meihua; He, Zhiyi (Frontiers in Medicine, 2021)
Background: To observe the effects of inhaled corticosteroids (ICS) and systemic corticosteroids (SCS) on the sputum microbiology of patients with AECOPD. Methods: The 16S rRNA sequencing results for sputum samples from 36 admitted AECOPD patients were analyzed using ICS or SCS on the basis of standard treatment; sputum samples were collected before and after treatment for 1 day, 7, and 14 days. Results: After 7 days of SCS treatment, the bacterial abundance of Sorangium, Acidibacter, and Fretibacterium decreased at the genus level. After 14 days of SCS treatment, the bacterial abundance of Prevotella_2, Bergeyella, Corynebacterium_1, and Ruminococcaceae_UCG-014 was decreased at the genus level, and an increase in the bacterial abundance of the Clostridiales_vadinBB60_group was observed at the family level. The linear discriminant analysis effect size (LEfSe) algorithm showed that after treatment for 14 days, Sphingobacterium increased in the SCS group, and Corynebacterium_1 (genus level), Bacillales (order level), and Lactobacillales (order level) decreased in the ICS group. However, the abundance of the above bacteria in each group of samples was <1%, suggesting that the two treatments may have similar effects on bacterial abundance. Alpha diversity analysis results showed that there was no significant difference in the ACE index, Chao1 index, Shannon index, or Simpson index between the ICS group and the SCS group. Beta diversity analysis showed that there was little difference in bacterial diversity among each group. BugBase predicted that although bacteria containing mobile elements in the SCS group decreased significantly compared with those in patients using ICS after treatment for 14 days, these two treatments had similar effects on other phenotype categories assigned to the bacterial contents. Conclusions: Our results show that ICS and SCS have remarkably similar effects on the sputum microbiome of AECOPD patients.